Development and test of CFD–DEM model for complex geometry: A coupling algorithm for Fluent and DEM - Liu, Daoyin; Bu, Changsheng; Chen, Xiaoping (Computers & chemical engineering, 2013)
•A CFD–DEM model is developed for simulations on complex geometries.•DEM is coupled with ANSYS/Fluent Eulerian multiphase model.•The current model is validated against a series of typical fluidization cases. CFD–Discrete Element Method (DEM) model is an effective approach for studying dense gas–solid flow in fluidized beds. In this study, a CFD–DEM model for complex geometries is developed, where DEM code is coupled with ANSYS/Fluent software through its User Defined Function. The Fluent Eulerian multiphase model is employed to couple with DEM, whose secondary phase acts as a ghost phase but just an image copy of DEM field. The proposed procedure preserves phase conservation and ensures the Fluent phase-coupled SIMPLE solver work stable. The model is used to simulate four typical fluidization cases, respectively, a single pulsed jet fluidized bed, fluidized bed with an immersed tube, fluidization regime transition from bubbling to fast, and a simplified two-dimensional circulating fluidized bed loop. The simulation results are satisfactory. The present approach provides an easily implemented and reliable method for CFD–DEM model on complex geometries.